Differences between the spectra of respiratory illnesses in children living in urban and rural environments - Dostálek, Miroslav; Průcha, Miroslav; Rychlíková, Eva; Pastorková, Anna; Šrám, Radim J (Central European Journal of Public Health, 2014)
A longitudinal study launched in 1994 within the framework of the Teplice Programme aimed at comparing the respiratory morbidity in children born (1994-1998) and living in the districts of Teplice (TE) and Prachatice (PRA) in the Czech Republic. Lists of all illnesses of 960 children from birth to 10 years of age were obtained from paediatric medical records. From 26,471 diagnoses (in ICD-10 codes), 34.7% were diagnoses of upper respiratory infections (URI, J00-02, J06), 11.3% of tonsillitis, 10.2% of influenza, 9.4% of bronchitis, 8.9% of laryngitis/tracheitis (J04), 2.7% of otitis media, and 0.5% of pneumonia. The more polluted district of Teplice was divided into two parts: the town itself (TE-town) and the rest of the district (TE-district). The cumulative incidence rates of the above respiratory illnesses per 100 children per 10 years were 2,212 in TE-town, 2,192 in PRA and 1,985 in TE-district. In the first two years of life, the children from TE-town had a significantly higher incidence of laryngitis/tracheitis, influenza, otitis media, and pneumonia and significantly lower incidence of bronchitis and tonsillitis than children living in PRA. The incidence rates of laryngitis/tracheitis and influenza in TE-town persisted as the highest among the three regions till the age of 10 years. The incidence rates of bronchitis (from the 1st to 5th year) and URI (from 4th to 10th year) were highest in children living in PRA. When compared to TE-town, children in TE-district had a higher incidence of upper respiratory infections (1-8 years) and lower incidence of bronchitis (6-8 years). Children in the district of Prachatice had a significantly higher prevalence of allergic rhinitis and a lower prevalence of wheezing than children in the district of Teplice. Thus, the three regions differed by the spectra of respiratory illnesses rather than by overall morbidity and, hypothetically, the effects of air pollution were obscurred by differences in the degree of urbanization.
Keywords: infekce dýchací soustavy; Urban Health; Acute Disease; Infant; Prevalence; dítě; předškolní dítě; novorozenec; longitudinální studie; lidé; Infant, Newborn; Respiratory Tract Infections; Incidence; prevalence; zdraví venkovských oblastí; incidence; kojenec; zdraví ve městech; Czech Republic; Child, Preschool; respirační alergie; Respiratory Hypersensitivity; Česká republika; Rural Health; akutní nemoc; Child; Longitudinal Studies; Humans